Effect of Concentration and Duration of Soaking Coconut Water on Germination of Black Soybean (Glycine max (L.) Merril) Seeds - A Miftakhurrohmat; Nayla Tania Rohma (Universitas Muhammadiyah Sidoarjo, 2022)
The purpose of this study was to determine the effect of concentration and duration of soaking coconut water on the germination of black soybean. Merril). This research was carried out in April-May 2021 in Wunut village, Porong sub-district, Sidoarjo. The experiment was arranged in a factorial manner in a randomized block design (RAK) consisting of 2 factors. The first factor is the soaking time, consisting of 6 hours, 12 hours, 18 hours. While the second factor is the concentration of coconut water, consisting of: 100ml aqua water as control, 25ml coconut water/ 75ml aqua water, 50ml coconut water/ 50ml aqua water, 75ml coconut water/ 25ml aqua water. Observation variables consisted of germination, plant height, leaf area, number of leaves, chlorophyll, wet weight, dry weight. The data were analyzed using ANOVA which was then followed up with the honest real difference test (BNJ), if the data obtained were very real then it was continued with the 1% BNJ test, but if the data obtained were real then it was continued with the 5% BNJ test. The res ults showed that the concentration and duration of immersion using coconut water showed a very significant interaction in the treatment, plant height at 14 DAP and 21 DAP, and showed a significant interaction in the number of leaves at 14 DAP and 28 DAP. The immersion time had a very significant effect on plant height at 28 DAP, while the concentration using coconut water had a very significant effect on germination.